An OT Background to Rom 8.22 - Tsumura, David Toshio (New Testament studies, 1994)
There has been much discussion in recent articles on the significance of the Spirit's ‘groaning’ in Rom 8.26. What has not been adequately treated is the OT background to v. 22. That verse reads as follows: οΪδαμεν γ⋯ρ ἵτι π⋯σα ⋯ κτ⋯στε σƲσΤεƲάζει κα⋯ συνωδ⋯νει ἄχρι το⋯ ν⋯ν and can be translated literally as follows:We know that the whole creation groans together and travails together until now.